Investigating Effects of Screen Layout Elements on Interface and Screen Design Aesthetics - Ahamed Altaboli; Yingzi Lin (Advances in Human-Computer Interaction)
A recent study suggested the use of the screen layout elements of balance, unity, and sequence as a part of a computational model of interface aesthetics. It is argued that these three elements are the most contributed terms in the model. In the current study, a controlled experiment was designed and conducted to systematically investigate effects of these three elements (balance, unity, and sequence) on the perceived interface aesthetics. Results showed that the three elements have significant effects on the perceived interface aesthetics. Significant interactions were also found among the three elements. A regression model relating the perceived visual aesthetics to the three elements was constructed. When validating the model using standard questionnaire scores of real web pages, high correlations were found between the values computed by the model and scores of questionnaire items related to visual layout of the web pages, indicating that layout-based measures are good at assessing the classical dimension of website aesthetics.